18th World Textile Conference (AUTEX 2018). (December 2018) - Unknown
Abstract : Dear Authors and Readers, It is a great pleasure for me to write this foreword for Autex 2018, 18th World Textile Conference, held in Istanbul, Turkey between 20-22 June 2018. Autex Conference brings together academicians, researchers, industry professionals, experts in textile field from all over the world and makes a significant contribution to realization of Autex objectives. It is a great honour for Istanbul Technical University, Textile Technologies and Design Faculty, to host this organization, which is one of the most important events in the field of textiles. The papers presented in the conference contributed to the knowledge and novelty in textile science in the sessions of Protective Textiles, Innovative Functional Textiles, Ecological and Environmental Textiles, Recycling and Life Cycle Analysis, Surface Functionalization and Coating, Smart, Interactive and Multifunctional Textiles, Technical Textiles, Composites and Membranes, Nanotechnology, Nanotextiles, Electrospinning, Textile and Clothing Machinery, Comfort Science, Modelling and Simulation, Fashion - Garment Industry and Marketing, Textile Testing, Measuring Technology, Fashion - Design and Garment Industry, Textile Economy, Textile Supply Chain Management, Advanced Fibers and Materials. Medical Textiles. Tissue Engineering, Implants, Textile Processing, Advanced Fibres and Materials, Modern Textile Education and Training, Innovation & Entrepreneurship, Fashion, Garment Industry, Simulation & Modeling. Seven plenary speakers made presentations in addition to the contributed papers. I deeply hope the proceedings included in this book will conribute as a reference book for novel studies and research. Prof. Dr. Fatma Kalaoğlu Conference Chair